Persian Refugees in Ancient Greece - Paolo A. Tuci (Pallas, 2020)
The paper examines the case of Persian men who fled the country and arrived as refugees in Greece. For the fifth century B.C. are attested Rhoesaces, Zopyrus and Amorges, while for the fourth an unnamed son of Pharnabazus, Artabazus, Amminapes and Sisines. Many details about their flight often remain obscure, but these episodes fit interestingly in the framework of international affairs. The main aspects that will be considered are the country in which they take refuge, the reasons for their flight, the relations with the country that hosts them and their role in international politics.